Visionary Leadership Model of School Principals in Improving the Quality of Education in Elementary Schools - Khilma Amil Diana (Yayasan Insan Cendekia Nusantara, 2025)
Research Background: his study examines the implementation of visionary leadership in Indonesian elementary schools, a context where educational quality remains uneven despite a high national enrollment rate. Although visionary leadership is recognized as a transformative approach capable of driving long-term school improvement, its application at the elementary level—particularly in resource-limited environments—has not been sufficiently explored. Methods: Using a qualitative case study design, data were collected through in-depth interviews, classroom observations, and documentation analysis involving principals, teachers, and staff in a public elementary school known for successfully applying visionary leadership. Data were analyzed using the Miles and Huberman interactive model to identify thematic patterns and contextual dynamics. Key Findings: Visionary leadership strengthens school culture, enhances teacher professionalism, improves learning quality, and encourages collective ownership of the school’s direction. However, challenges persist, including resistance to change, limited managerial literacy, inadequate facilities, and inconsistent stakeholder support. Contribution: The literature by highlighting the specific conditions, strategies, and adaptations required for visionary leadership to function effectively at the elementary level—an area previously underrepresented in research. It also provides a contextualized understanding of how visionary leadership can be realistically enacted amid socio-cultural constraints and resource limitations. Conclusion: The success of visionary leadership depends on sustained communication, collaborative vision-building, capacity development, and systematic support from educational authorities. Strengthening practical, context-based leadership training and stakeholder involvement is essential to improving the quality of elementary education